THE EFFECT OF THE IMPLEMENTATION OF OCCUPATIONAL SAFETY HEALTH (K3) AND WORK DISCIPLINE PROGRAM IMPLEMENTATION ON THE WORK PRODUCTIVITY OF EMPLOYEES IN THE PRODUCTION SECTION AT THE PALM OIL FACTORY (PKS) PT. CITRA RIAU SARANA II KUANTAN SINGINGI REGENCY - Putri, Apri Agnesta; Karneli, Okta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research is motivated by business competition in the era of globalization which requires companies to compete to produce quality products and maintain their existence. Human resources are an important role for the success of the PT. Citra Riau Sarana II Kuantan Singingi Regency which needs to be maintained and developed to increase work productivity. This study aims to determine the level of work productivity of employees in the production division at the PT. Citra Riau Sarana II Kuantan Singingi Regency. This study used a questionnaire as a data collection tool which was distributed to 73 respondents to production employees. In this research, the method used is descriptive and quantitative. The data obtained from the results of interviews and the distribution of questionnaires/questionnaires were then tested with statistics through the SPSS program. The analytical method used in this research is simple and multiple regression analysis, and through validity and reliability tests. In this study the results obtained are that Occupational Safety and Health (K3) has a positive and significant effect on Work Productivity, Work Discipline has a positive and significant effect on Work Productivity and that Occupational Safety and Health (K3) and Work Discipline have a positive and significant impact on Productivity. Employees of the Production Division of the Palm Oil Mill PT. Citra Riau Sarana II Kuantan Singingi Regency Keywords: Implementation of Occupational Safety Health (K3) Program, Work Discipline, Work Productivity